Click Here: Recommended Books for ICSE Self Study

Question 1: Evaluate:

i) 3 \begin{bmatrix}  5   \\ -2  \end{bmatrix} =  \begin{bmatrix}  15   \\ -6  \end{bmatrix}

ii) 7  \begin{bmatrix}  -1 & 2  \\ 0 & 1 \end{bmatrix} = \begin{bmatrix}  -7 & 14  \\ 0 & 7 \end{bmatrix}

iii) 2 \begin{bmatrix}  -1 & 0  \\ 2 & -3 \end{bmatrix} + \begin{bmatrix}  3 & 3  \\ 5 & 0 \end{bmatrix} =  \begin{bmatrix}  -2 & 0  \\ 4 & -6 \end{bmatrix} + \begin{bmatrix}  3 & 3  \\ 5 & 0 \end{bmatrix} =  \begin{bmatrix}  1 & 3  \\ 9 & -6 \end{bmatrix}

iv) 6 \begin{bmatrix}  3   \\ 2 \end{bmatrix} - 2 \begin{bmatrix}  -8  \\ 1 \end{bmatrix} =  \begin{bmatrix}  18   \\ 12 \end{bmatrix} -  \begin{bmatrix}  -16  \\ 2 \end{bmatrix} =  \begin{bmatrix}  34  \\ -14 \end{bmatrix}

\\

Question 2: Find x \ and \  y if

i) 3 \begin{bmatrix}  4   & x  \end{bmatrix} +2  \begin{bmatrix}  y   & -3  \end{bmatrix} = \begin{bmatrix}  10   & 0  \end{bmatrix} 

ii)  x \begin{bmatrix}  -1   \\ 2 \end{bmatrix} -4 \begin{bmatrix}  -2   \\ y \end{bmatrix} =  \begin{bmatrix}  7   \\ -8 \end{bmatrix} 

Answer:

i) 3 \begin{bmatrix}  4   & x  \end{bmatrix} +2  \begin{bmatrix}  y   & -3  \end{bmatrix} = \begin{bmatrix}  10   & 0  \end{bmatrix} 

\Rightarrow  \begin{bmatrix}  12   & 3x  \end{bmatrix} + \begin{bmatrix}  2y   & -6  \end{bmatrix} = \begin{bmatrix}  10   & 0  \end{bmatrix} 

Therefore

12+2y = \ 10  \ or y = -1 

3x-6=0 \ or \  x = 2 

ii)  x \begin{bmatrix}  -1   \\ 2 \end{bmatrix} -4 \begin{bmatrix}  -2   \\ y \end{bmatrix} =  \begin{bmatrix}  7   \\ -8 \end{bmatrix} 

  \begin{bmatrix}  -x   \\ 2x \end{bmatrix} - \begin{bmatrix}  -8   \\ 4y \end{bmatrix} =  \begin{bmatrix}  7   \\ -8 \end{bmatrix} 

Therefore

  -x+8 = 7 \ or \ x = 1  

  2x-4y = -8 \ or \ y = 10  

\\

Question 3: Given  A =  \begin{bmatrix}  2 & 1   \\ 3 & 0 \end{bmatrix}    B =  \begin{bmatrix}  1 & 1   \\ 5 & 2 \end{bmatrix}    C =  \begin{bmatrix}  -3 & -1   \\ 0 & 0 \end{bmatrix}   , Find:

i)   2A-3B+C   

ii)   A+2C-B   

Answer:

i)   2A-3B+C   

 2 \begin{bmatrix}  2 & 1   \\ 3 & 0 \end{bmatrix} - 3 \begin{bmatrix}  1 & 1   \\ 5 & 2 \end{bmatrix} +   \begin{bmatrix}  -3 & -1   \\ 0 & 0 \end{bmatrix}   

 =  \begin{bmatrix}  4 & 2   \\ 6 & 0 \end{bmatrix} -  \begin{bmatrix}  3 & 3   \\ 15 & 6 \end{bmatrix} +   \begin{bmatrix}  -3 & -1   \\ 0 & 0 \end{bmatrix}   

 =  \begin{bmatrix}  -2 & -2   \\ -9 & -6 \end{bmatrix}   

ii)   A+2C-B   

 \begin{bmatrix}  2 & 1   \\ 3 & 0 \end{bmatrix} + 2 \begin{bmatrix}  -3 & -1   \\ 0 & 0 \end{bmatrix} -  \begin{bmatrix}  1 & 1   \\ 5 & 2 \end{bmatrix}   

 = \begin{bmatrix}  2 & 1   \\ 3 & 0 \end{bmatrix} +  \begin{bmatrix}  -6 & -2   \\ 0 & 0 \end{bmatrix} -  \begin{bmatrix}  1 & 1   \\ 5 & 2 \end{bmatrix}  

 = \begin{bmatrix}  -5 & -2   \\ -2 & -2 \end{bmatrix}  

\\

Question 4: If  \begin{bmatrix}  4 & -2   \\ 4 & 0 \end{bmatrix} +3A = \begin{bmatrix}  -2 & -2   \\ 1 & -3 \end{bmatrix} , Find A

Answer:

\begin{bmatrix}  4 & -2   \\ 4 & 0 \end{bmatrix} +3A = \begin{bmatrix}  -2 & -2   \\ 1 & -3 \end{bmatrix}

\Rightarrow 3A = \begin{bmatrix}  -2 & -2   \\ 1 & -3 \end{bmatrix}  - \begin{bmatrix}  4 & -2   \\ 4 & 0 \end{bmatrix}

\Rightarrow 3A = \begin{bmatrix}  -6 & 0   \\ -3 & -3 \end{bmatrix} 

\Rightarrow A = \begin{bmatrix}  -2 & 0   \\ -1 & -1 \end{bmatrix} 

\\

Question 5: Given  A =  \begin{bmatrix}  1 & 4   \\ 2 & 3 \end{bmatrix}   ,   B =  \begin{bmatrix}  -4 & -1   \\ -3 & -2 \end{bmatrix}   , Find

i) 2A+B  

ii) Matrix C  such that C+B = \begin{bmatrix}  0 & 0   \\ 0 & 0 \end{bmatrix}  

Answer:

i) 2A+B  

 \Rightarrow 2  \begin{bmatrix}  1 & 4   \\ 2 & 3 \end{bmatrix} + \begin{bmatrix}  -4 & -1   \\ -3 & -2 \end{bmatrix}  = \begin{bmatrix}  -2 & 7   \\ 1 & 4 \end{bmatrix}    

ii) C+B = \begin{bmatrix}  0 & 0   \\ 0 & 0 \end{bmatrix}  

C = \begin{bmatrix}  0 & 0   \\ 0 & 0 \end{bmatrix} - \begin{bmatrix}  -4 & -1   \\ -3 & -2 \end{bmatrix}   

C = \begin{bmatrix}  4 & 1   \\ 3 & 2 \end{bmatrix}

\\

Question 6: If 2 \begin{bmatrix}  3 & x   \\ 0 & 1 \end{bmatrix} + 3 \begin{bmatrix}  1 & 3   \\ y & 2 \end{bmatrix} = \begin{bmatrix}  z & -7   \\ 15 & 8 \end{bmatrix} , Find the value of x, \ y, \ and \ z .

Answer: 

2 \begin{bmatrix}  3 & x   \\ 0 & 1 \end{bmatrix} + 3 \begin{bmatrix}  1 & 3   \\ y & 2 \end{bmatrix} = \begin{bmatrix}  z & -7   \\ 15 & 8 \end{bmatrix}

 \Rightarrow \begin{bmatrix}  6 & 2x   \\ 0 & 2 \end{bmatrix} + \begin{bmatrix}  3 & 9   \\ 3y & 6 \end{bmatrix} = \begin{bmatrix}  z & -7   \\ 15 & 8 \end{bmatrix}

 \Rightarrow \begin{bmatrix}  9 & 2x+9   \\ 3y & 8 \end{bmatrix}= \begin{bmatrix}  z & -7   \\ 15 & 8 \end{bmatrix}

Therefore

z=9

2x+9 = -7 \ or \ x = -8

3y = 15 \ or \ y = 5

\\

Question 7: Given  A =  \begin{bmatrix}  -3 & 6   \\ 0 & -9 \end{bmatrix}   and A^t is the transpose matrix. Find:

i) 2A + 3A^t   

ii) 2A^t-3A   

iii) \frac{1}{2} A - \frac{1}{3}A^t   

iv) A^t - \frac{1}{3}A   

Answer:

If  A =  \begin{bmatrix}  -3 & 6   \\ 0 & -9 \end{bmatrix}  

Then  A^t =  \begin{bmatrix}  -3 & 0   \\ 6 & -9 \end{bmatrix}  

i) 2A + 3A^t   

2 \begin{bmatrix}  -3 & 6   \\ 0 & -9 \end{bmatrix} +3 \begin{bmatrix}  -3 & 0   \\ 6 & -9 \end{bmatrix} = \begin{bmatrix}  -15 & 12   \\ 18 & -45 \end{bmatrix}

ii) 2A^t-3A   

2 \begin{bmatrix}  -3 & 0   \\ 6 & -9 \end{bmatrix} - 3 \begin{bmatrix}  -3 & 6   \\ 0 & -9 \end{bmatrix} = \begin{bmatrix}  3 & -18   \\ 12 & 9 \end{bmatrix}

iii) \frac{1}{2} A - \frac{1}{3}A^t   

\frac{1}{2}\begin{bmatrix}  -3 & 6   \\ 0 & -9 \end{bmatrix} - \frac{1}{3}\begin{bmatrix}  -3 & 0   \\ 6 & -9 \end{bmatrix} =\begin{bmatrix}  -\frac{1}{2} & 3   \\ -2 & -\frac{3}{2} \end{bmatrix}   

iv) A^t - \frac{1}{3}A   

\begin{bmatrix}  -3 & 0   \\ 6 & -9 \end{bmatrix}-\frac{1}{3} \begin{bmatrix}  -3 & 6   \\ 0 & -9 \end{bmatrix}= \begin{bmatrix}  -2 & -2   \\ 6 & -6 \end{bmatrix}

\\

Question 8: Given  A =  \begin{bmatrix}  1 & 1   \\ -2 & 0 \end{bmatrix}   and  B =  \begin{bmatrix}  2 & -1   \\ 1 & 1 \end{bmatrix}   . Solve for

i)  X+2A=B  

ii)  3X+B+2A=0  

iii)  3A-2X=X-2B  

Answer:

i)      X+2A=B  

X = B-2A   

X= \begin{bmatrix}  2 & -1   \\ 1 & 1 \end{bmatrix}-2 \begin{bmatrix}  1 & 1   \\ -2 & 0 \end{bmatrix} = \begin{bmatrix}  0 & -3   \\ 5 & 1 \end{bmatrix}

ii)     3X+B+2A=0  

X = \frac{-1}{3}(B+2A)   

X = \frac{-1}{3}(\begin{bmatrix}  2 & -1   \\ 1 & 1 \end{bmatrix}+2\begin{bmatrix}  1 & 1   \\ -2 & 0 \end{bmatrix}) = \begin{bmatrix}  \frac{4}{3} & \frac{1}{3}   \\ -1 & \frac{1}{3} \end{bmatrix}

iii)    3A-2X=X-2B  

X = \frac{1}{3} (3A+2B)   

X = \frac{1}{3} (3\begin{bmatrix}  1 & 1   \\ -2 & 0 \end{bmatrix} +2\begin{bmatrix}  2 & -1   \\ 1 & 1 \end{bmatrix}) = \begin{bmatrix}  \frac{-7}{3} & \frac{1}{3}   \\ \frac{-4}{3} & \frac{2}{3} \end{bmatrix}

\\

Question 9: If  M =  \begin{bmatrix}  0   \\ 1 \end{bmatrix}    and   N =  \begin{bmatrix}  0   \\ 1 \end{bmatrix}   , show that 3M+5N=\begin{bmatrix}  5   \\ 3 \end{bmatrix}  

Answer: 

3M+5N=3\begin{bmatrix}  0   \\ 1 \end{bmatrix} +5\begin{bmatrix}  0   \\ 1 \end{bmatrix} =\begin{bmatrix}  5   \\ 3 \end{bmatrix} 

Hence proved.

Question 10: If I is the unit matrix of order 2 \times 2 , find the matrix M such that

i) M-2I= 3\begin{bmatrix}  -1 & 0   \\ 4 & 1 \end{bmatrix}  

ii) 5M+3I= 4\begin{bmatrix}  2 & -5   \\ 0 & -3 \end{bmatrix}  

Answer:

Given I is a unit matrix of order 2 \times 2 , we have

 I =  \begin{bmatrix}  1 & 0   \\ 0 & 1 \end{bmatrix}  

i)   M = 2\begin{bmatrix}  1 & 0   \\ 0 & 1 \end{bmatrix} + 3\begin{bmatrix}  -1 & 0   \\ 4 & 1 \end{bmatrix}  = \begin{bmatrix}  -1 & 0   \\ 12 & 5 \end{bmatrix}  

ii) M= \frac{1}{5} (-3\begin{bmatrix}  1 & 0   \\ 0 & 1 \end{bmatrix} + 4\begin{bmatrix}  2 & -5   \\ 0 & -3 \end{bmatrix})  =\begin{bmatrix}  1 & -4   \\ 0 & -3 \end{bmatrix} 

\\

Question 11. If \begin{bmatrix} 1 & 4 \\ -2 & 3 \end{bmatrix} +2M = 3 \begin{bmatrix} 3 & 2 \\ 0 & -3 \end{bmatrix} , find the matrix M

Answer:

2M =3 \begin{bmatrix}  3 & 2   \\ 0 & -3 \end{bmatrix} - \begin{bmatrix}  1 & 4   \\ -2 & 3 \end{bmatrix}

2M =\begin{bmatrix}  9 & 6   \\ 0 & -9 \end{bmatrix} - \begin{bmatrix}  1 & 4   \\ -2 & 3 \end{bmatrix} =  \begin{bmatrix}  8 & 2   \\ 2 & -12 \end{bmatrix}

Therefore M =\begin{bmatrix}  4 & 1   \\ 1 & -6 \end{bmatrix} 

\\

Advertisements